Racialized Bodies and the Violence of the Setting. Issue 3 (3rd July 2019) - Butler, Daniel G.
ABSTRACT: Turning to object relations psychoanalysis and Black critical theory, I argue that the violence of racialization works in and through clinical and national settings. The setting is theorized in terms of its phantasmatic and phantomatic dimensions: The former refers to phantasies that ensnare certain bodies in a mythologized past, while the latter refers to the irreducibly material histories that those phantasies fail to ensnare (i.e., the phantom world). The case of a Confederate statue's proposed removal is used to illustrate the tension between phantasm/phantom at a national level, while Searles's writings demonstrate the interplay of phantasm/phantom in a clinical context.